IMPLEMENTASI TANGGUNGJAWAB REKLAMASI PERTAMBANGAN TIMAH DI PULAU BELITUNG - Haryadi, Dwi; Darwance, Darwance; Salfutra, Reko Dwi (PROGRESIF: Jurnal Hukum, 2018)
Mining is one of the sectors that becomes an economic country’s support until now. Environmental issues is kind of difficult things and can’t even be separated from mining activities. Belitung island is as part of the largest tin-producing province in Indonesia that has been exploited since the 18 century. It also has experienced the environmental crisis as well as other mining areas has in Indonesia. This research is conducted as an effort to discover and unravel the problematic implementation of reclamation on the ex-tin mine’s land in Belitung Island by using a conceptual approach and legislative approach. Based on the observation’s result, it shows that the reclamation’s result in Belitung Island has not been successful. Data from PT Timah (Persero) Tbk about the reclamation in Belitung Island also shows that the realization is far from the plan. There is no target that achieved successfully every year, also there is no reclamation that reaches 50 percent, the maximum is only 25 percent in 2016. th